Pengimplementasian Metode Simple Multi Attribute Rating Technique pada Sistem Pendukung Keputusan: Literatur Review - Adha, Hafid Dwi; Zen, Lova Endriani; Hanim, Hafizah; Prasetyo, Haditya; Novi (Jurnal Informatika Ekonomi Bisnis, 2025)
The rapid development of technology today paves the way for the birth of various scientific inventions. Technology can assist decision-makers in determining a decision to be reached. One technology that can be utilized is a decision support system. Decision support systems can help reduce uncertainty and make the decision-making process more efficient. The Simple Multi-Attribute Rating Technique method is one of them, a method that can be applied to decision support systems. This study aims to be a literature review that can help researchers apply the Simple Multi-Attribute Rating Technique method in further research. This study presents 10 articles from national and international accredited journals that use the Simple Multi-Attribute Rating Technique method in their research. The Simple Multi-Attribute Rating Technique method can be used in various case studies, evaluation of student final assignment guidance, identification of employee performance, for selecting the best employees, determining sanctions, and selecting the best cafes in an area.